Blow-ups in non-reductive GIT and moduli spaces of unstable vector bundles over curves - Qiao, Y (2022)
We use non-reductive geometric invariant theory (NRGIT) to study a moduli problem involving pure sheaves of fixed Harder-Narasimhan type. The construction of moduli spaces for such sheaves can be reduced to the construction of NRGIT quotients of subschemes of Quot schemes. Hitherto NRGIT has been developed only for actions on varieties, whereas Quot schemes are not varieties.